Answer:
Step-by-step explanation:
y = kx ;
k = [tex]\frac{y}{x}[/tex] ; x = [tex]\frac{y}{k}[/tex]
~~~~~~~~~~~~~
k = [tex]\frac{1}{2}[/tex] ÷ 1 = [tex]\frac{1}{2}[/tex]
[tex]y_{1}[/tex] = [tex]\frac{1}{2}[/tex] × ( - 8 ) = - 4
[tex]y_{2}[/tex] = [tex]\frac{1}{2}[/tex] × ( - 4 ) = - 2
[tex]y_{3}[/tex] = [tex]\frac{1}{2}[/tex] × 2 = 1
[tex]x_{5}[/tex] = [tex]\frac{1}{3}[/tex] ÷ [tex]\frac{1}{2}[/tex] = [tex]\frac{2}{3}[/tex]
[tex]x_{6}[/tex] = - [tex]\frac{1}{4}[/tex] ÷ [tex]\frac{1}{2}[/tex] = - [tex]\frac{1}{2}[/tex]
[tex]x_{7}[/tex] = 0
( x , y ) : ( - 8 , - 4 ), ( - 4 , - 2 ), ( 2 , 1 ), ( 1 , [tex]\frac{1}{2}[/tex] ), ( [tex]\frac{2}{3}[/tex] , [tex]\frac{1}{3}[/tex] ), ( - [tex]\frac{1}{2}[/tex] , - [tex]\frac{1}{4}[/tex] ), ( 0 , 0 )